Effect of cement type and limestone particle size on the durability of steam cured self-consolidating concrete. (July 2017) - Panesar, D.K.; Aqel, M.; Rhead, D.; Schell, H.
Abstract: This paper describes a laboratory program to investigate the influence of cement and limestone filler (LF) particle size on the hardened properties and durability performance of steam cured self-consolidating concrete. In addition, the interplay between cement type and LF particle size was investigated. CSA (Canadian Standards Association) Type GU (General Use) and HE (High Early-strength) cements were used with 5% silica fume (SF) [1]. The water-to-cement ratio was 0.34. LF with two nominal particle sizes of 17 μm and 3 μm, which correspond to Blaine fineness of 475 and 1125 m 2 /kg, respectively, were used. In addition to fresh concrete properties, hardened properties including compressive strength, elastic modulus, ultrasonic pulse velocity and density were measured at 12 h and 16 h, and at 3, 7 and 28 days. Indicators of durability performance including rapid chloride permeability testing (RCPT), sulfate resistance, linear shrinkage, salt scaling resistance and freeze-thaw resistance were evaluated. The results showed that LF improved the 12 and 16-h strength with no influence on later age strength (i.e., 3–28 days). The linear shrinkage and RCPT decreased with the addition of LF. This reduction was linked to the production of calcium mono-carboaluminate. LF did not impact the sulfate resistance, salt scaling resistance or freeze-thaw resistance of concrete.